SOSIALISASI PENCEGAHAN COVID-19 DENGAN PENERAPAN PROTOKOL KESEHATAN DI KELURAHAN GAMBESI - Abdul Gaus; Nurmaiyasa Marsaoly (Universitas Khairun, 2021)
The COVID-19 pandemic has had an impact on various sectors, including the education sector, during the pandemic teaching and learning activities which are usually carried out face-to-face in the classroom, laboratories can no longer be carried out. This has an impact on the community around the campus, which has been relying on activities created by the presence of students who are studying. During the pandemic, community activities decline, boarding houses are empty and uninhabited, food stalls are deserted, printing, transportation and other sectors seem to have stopped their activities. The government has implemented a new normal so that people can carry out their activities again but still have to enforce health protocols to prevent clusters of spreading COVID-19. Socialization on the importance of maintaining distance, wearing masks and washing hands is one of the efforts to provide understanding to the public so that they remain vigilant and enforce strict health protocols so that new clusters do not arise in the spread of COVID-19. Socialization, distribution of masks, hand sanitizers and health checks have had an impact on increasing awareness in the community in the campus environment about the importance of enforcing health protocols to prevent the spread of COVID-19 and the importance of maintaining health..